1991
DOI: 10.1177/014616729101700212
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Advertising Appeal on Perceptions of Product Quality

Abstract: In Study 1, high and low self-monitors either listened to music on a cassette tape or sampded a cola product after observing either an image- or a quality-oriented advertisement for the product. High self-monitors rated the quality of the products higher than low self-monitors after suing the image-oriented advertisements, and low self-monitors rated the quality of the products higher than high self-monitors after seeing the quality-oriented advertisements. In Study 2, high and low self-monitors -sorted ads th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 7 publications
6
49
0
1
Order By: Relevance
“…39 40 The concept of attitude function has been studied in relation to attitudes towards victims of AIDS, 41 attitudes towards homosexuals, 42 attitudes towards automobiles, 43 44 and attitudes towards advertising of consumer products. [45][46][47][48][49][50][51][52] As applied to smoking, this suggests that it is not only useful to know that the target group has positive attitudes towards smoking, but also to be aware of why that group has positive attitudes towards smoking. An adolescent may hold positive attitudes towards smoking because she wishes to fit in with her peers, to keep her body weight low, or because she enjoys the physiological effects of smoking.…”
Section: Focus On Relevant Attitudes Of the Target Groupmentioning
confidence: 99%
“…39 40 The concept of attitude function has been studied in relation to attitudes towards victims of AIDS, 41 attitudes towards homosexuals, 42 attitudes towards automobiles, 43 44 and attitudes towards advertising of consumer products. [45][46][47][48][49][50][51][52] As applied to smoking, this suggests that it is not only useful to know that the target group has positive attitudes towards smoking, but also to be aware of why that group has positive attitudes towards smoking. An adolescent may hold positive attitudes towards smoking because she wishes to fit in with her peers, to keep her body weight low, or because she enjoys the physiological effects of smoking.…”
Section: Focus On Relevant Attitudes Of the Target Groupmentioning
confidence: 99%
“…Individuals who are high in self-monitoring may behave more sensitively regarding mental processes, guiding people and identifying the events. They often try to exhibit behaviors consistent with their social status (DeBono & Packer, 1991). Individuals high in self-monitoring attempt to display their talents to their friends based on the skills they have and tend to improve themselves in this direction.…”
Section: Introductionmentioning
confidence: 99%
“…High self-monitors play different roles towards the demands of the society they have joined rather than reflecting their inner world, while low self-monitors seem not to abstain from reflecting their inner world (Koç, 2009). Individuals with high levels of self-monitoring are inclined to scrutinize the events more compared to people with low levels of self-monitoring and they use subjective norms more heavily (DeBono & Omoto, 1993;DeBono & Packer, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that high and low self-monitors respond differently to advertising, through a variation in concern for appearance (De Bono & Packer, 1991;Snyder & DeBono, 1985). Studies have also shown that high self-monitors tended toward favoring products depicted in image-based advertising and low self-monitors tended toward favoring products depicted in quality-based advertising (DeBono & Packer, 1991). Snyder (1987) has suggested that self-monitoring affects consumer behavior because it is associated with the degree of interest in maintaining a front, through products (such as fashion clothing) that are used as props because they convey an image of the self to other people.…”
Section: Self-monitoring and Consumer Behaviormentioning
confidence: 99%
“…The self-monitoring scale has generated a substantial body of research that continues to develop, particularly in psychology. This development and growth is also starting to occur in consumer research, with researchers such as Bell, Holbrook, and Solomon (1991), Becherer and Richard (1978), DeBono and Packer (1991), Snyder and DeBono (1985), and Shavitt, Lowrey, and Han (1992) using self-monitoring in their studies on aspects of consumer behavior. This research includes a limited number of evaluations of the scale that include both supportive and critical evaluations.…”
Section: The Snyder Self-monitoring Scalementioning
confidence: 99%